Teachers' Efforts in Applying Movement and Songs to Autistic Children in Developing Gross Physical Motor Skills in the 5-6 Year Age Group at As Salam Branti Kindergarten - Astria Ningrum; Muhammad Yusuf; Ferdian Utama (CV. Creative Tugu Pena, 2025)
This study aims to describe the efforts of teachers in applying movement and song to children with autism in developing gross motor physical abilities in the 5-6 year old group at As Salam Branti Kindergarten. This study used a qualitative descriptive approach with a field research type. The research subjects were determined through a purposive sampling technique involving the principal, group B teachers, and one autistic child. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the teachers' efforts were carried out in a structured manner through the stages of preparation and song selection, individual approaches, gradual implementation of activities, and evaluation and adjustment of methods. The application of movement and song has been proven to have a positive impact on the gross motor development of children with autism, characterized by improved body movement coordination, balance, use of both hands, and the ability to follow simple activities in a more directed manner. Thus, the movement and song method can be an effective and adaptive learning strategy in supporting the gross motor physical development of autistic children in early childhood education.